Micrometric segregation of fluorescent membrane lipids: relevance for endogenous lipids and biogenesis in erythrocytes - D'Auria, Ludovic (The American Society for Biochemistry and Molecular Biology, 2013)
Micrometric membrane lipid segregation is controversial. We addressed this issue in attached erythrocytes and found that fluorescent boron dipyrromethene (BODIPY) analogs of glycosphingolipids (GSLs) [glucosylceramide (BODIPY-GlcCer) and monosialotetrahexosylganglioside (GM1BODIPY)], sphingomyelin (BODIPY-SM), and phosphatidylcholine (BODIPY-PC inserted into the plasma membrane spontaneously gathered into distinct submicrometric domains. GM1BODIPY domains colocalized with endogenous GM1 labeled by cholera toxin. All BODIPY-lipid domains disappeared upon erythrocyte stretching, indicating control by membrane tension. Minor cholesterol depletion suppressed BODIPY-SM and BODIPY-PC but preserved BODIPY-GlcCer domains. Each type of domain exchanged constituents but assumed fixed positions, suggesting self-clustering and anchorage to spectrin. Domains showed differential association with 4.1R versus ankyrin complexes upon antibody patching. BODIPY-lipid domains also responded differentially to uncoupling at 4.1R complexes [protein kinase C (PKC) activation] and ankyrin complexes (in spherocytosis, a membrane fragility disease). These data point to micrometric compartmentation of polar BODIPY-lipids modulated by membrane tension, cholesterol, and differential association to the two nonredundant membrane:spectrin anchorage complexes. Micrometric compartmentation might play a role in erythrocyte membrane deformability and fragility.